Edgar Allan - Neufeld, John. (New York : Signet, 1969)
The Reverend Fickett, his wife, and four children live comfortably in a privileged and conservative small town in California. They adopt Edgar Allan, a black child. The impact on their community and family is described.
Book Links (A.L.A.).
Elem. School Library Collection.
Notable/Best Books (A.L.A.).
5.6
10-12
5-8
Keywords: African Americans -- Fiction; Family -- Fiction; Race relations -- Fiction; African Americans -- Fiction; Family problems -- Fiction; Race relations -- Fiction